Development of an Online Teaching and Learning Model for Nursing Practicum in Sick Children as a Substitute for Clinical Practice During the COVID-19 Pandemic - Chaisri, Piyada; Kautrakool, Ampaiporn; Benjakul, Wunvimul (Journal of Research in Nursing-Midwifery and Health Sciences, 2024)
Objective: This research aimed to develop an online pedagogical model tailored to pediatric nursing practicum for sick children, serving as an alternative to traditional clinical practice amidst the COVID-19 pandemic. Methods: The process comprised four phases based on Dick and Carey learning design including 1) analyze challenges of teaching and learning in theclinical setting during the COVID-19 pandemic 2) desing an online teaching and learning model for pediatric nursing practicum in sick children to substitute clinical nursing practice 3) implement online learning model for pediatric nursing practicum in sick children. The research cohort consisted of 60 fourth-year nursing students enrolled in the pediatric nursing practicum course during the first semester of the year 2021 and 4) evaluate the developed online learning model. The research instrumentation included guideline for a group meeting of instructors and satisfaction questionnaire. The content validity index of this questionnaire was determined to be .96 The data were analysed using descriptive statistics. Results: 1. Development of online learning was needed as a substitute for clinical practice during the COVID-19 pandemic. 2. The online learning model for pediatric nursing practicum encompasses three distinct phases facilitated through a digital platform including 1) The preparatory phase, encompasses readiness assessments and adequate preparation of instructors, learners, and learning materials, 2) The learning phase integrates case assignments, nursing shift handovers, pre-post conference sessions, medication administration procedures, and reflective exercises, and 3) The evaluation phase focuses on a comprehensive assessment of the learning experience. 3. This model was implemented in students that was divided into eight groups (eight person/group) for three days. 4. This study revealed a high level of participants’s satisfaction with the various components of the online learning model (M = 4.20, SD = 0.41). Conclusions: The online learning model for pediatric nursing practicum in sick children can be used as a substitute for pediatric nursing placement during COVID-19.